The Influence of Consumer Knowledge and Green Advertising on the Decision to Use Plastic Bags - Adi Utama (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Plastic waste is a serious problem in Indonesia. Synthetic plastic or non-degradable plastic is a cause of waste and a trigger for environmental pollution. Plastic waste is the most discarded waste by humans because many people use plastic for their daily needs, whether it be individuals, shops, or large companies. The research objectives are to obtain the results of the study consumer knowledge about the dangers of plastic, to find out the analysis of the implementation of green advertisement, to know how the consumer's decision to use plastic bags, to determine the analysis of the influence of consumer knowledge on use decisions and to determine the analysis of the effect of green advertising on decisions to use plastic. The research method used was descriptive verificative with data collection techniques through literature and distributing questionnaires. The results showed that the consumer knowledge about the dangers of plastic shows is in the tofu category which shows that consumers know how dangerous plastic bags are. Consumer knowledge and green advertising do not affect the decision to use plastic. This indicates that consumer knowledge and green advertising have not been able to explain the use of plastic bags.